The concept and the elementary structure of the mechanism of the procedural and legal regulation - Атаманчук, І. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article is carried out the analysis of the scientific approaches to the understanding of mechanism ofthe legal adjusting, its signs and elementary construction. From description of general category of mechanismof the legal adjusting an author passes to the analysis of procedural legal mechanism, gives it an attemptof formation of determination of mechanism of the procedural legal adjusting on the base of selection of itsstructural elementsiminal code of Ukraine). Discusses issues of conformity of the criminal and air law terminologyin Ukraine.